Iodinated cyanine dye-based nanosystem for synergistic phototherapy and hypoxia-activated bioreductive therapy. (31st December 2022) - Dong, Yunxia; Zhou, Ling; Shen, Zijun; Ma, Qingming; Zhao, Yifan; Sun, Yong; Cao, Jie
Abstract: Photodynamic therapy (PDT) has been applied in cancer treatment by utilizing reactive oxygen species (ROS) to kill cancer cells. However, the effectiveness of PDT is greatly reduced due to local hypoxia. Hypoxic activated chemotherapy combined with PDT is expected to be a novel strategy to enhance anti-cancer therapy. Herein, a novel liposome (LCT) incorporated with photosensitizer (PS) and bioreductive prodrugs was developed for PDT-activated chemotherapy. In the design, CyI, an iodinated cyanine dye, which could simultaneously generate enhanced ROS and heat than other commonly used cyanine dyes, was loaded into the lipid bilayer; while tirapazamine (TPZ), a hypoxia-activated prodrug was encapsulated in the hydrophilic nucleus. Upon appropriate near-infrared (NIR) irradiation, CyI could simultaneously produce ROS and heat for synergistic PDT and photothermal therapy (PTT), as well as provide fluorescence signals for precise real-time imaging. Meanwhile, the continuous consumption of oxygen would result in a hypoxia microenvironment, further activating TPZ free radicals for chemotherapy, which could induce DNA double-strand breakage and chromosome aberration. Moreover, the prepared LCT could stimulate acute immune response through PDT activation, leading to synergistic PDT/PTT/chemo/immunotherapy to kill cancer cells and reduce tumor metastasis. Both in vitro and in vivo results demonstrated improved anticancer efficacy of LCT compared with traditional PDT or chemotherapy. It is expected that these iodinated cyanine dyes-based liposomes will provide a powerful and versatile theranostic strategy for tumor target phototherapy and PDT-induced chemotherapy.